DEVELOPMENT OF CURRICULA FOR INCLUSIVE AND ACCESSIBLE TOURISM: EXPERIENCES FROM THE ERASMUS+ PROJECT IN-TOUR (Proceedings of the International Conference on Education, 2022)
Inclusivity is a pertinent driver for the development of the tourism industry, but the concept has not been sufficiently reflected. It is a way of making sure that everyone who visits or utilizes a service feels comfortable and welcome. ‘Inclusive’ or ‘accessible tourism’ or ‘tourism for all’ as a holistic concept is a social right which concerns all citizens. This not only challenges tourism companies who try to integrate inclusive concepts in their services according to the needs and accessibility requirements of disabled customers, but this has also a significant impact on international and national tourism policy development. Moreover, the European Commission has recently conducted research that indicates that there is a significant gap in the supply of accessible services for tourists with special needs. The gap is likely to increase over the next few years, and it is estimated that at least 2.3 million tourism enterprises will need to provide accessible services to meet future demand. Against this backdrop, the Erasmus+ IN-TOUR Project intends to fill this gap in the European training system by providing quality education and training on tourism for all. This project aims to create competency-based, flexible and modular VET- and higher education curricula for ‘Inclusive Tourism Manager’ and ‘Inclusive Tourism Frontline Staff’ on EQF levels 5 to 7 that can be implemented in the different EU Member States. Against this backdrop, this paper will present its approach for the curriculum development, local piloting and evaluation. Conclusions will be drawn regarding practical implications to enhance the competences of different stakeholders in tourism like leisure facilities, hotels and destinations and to future research direction to support the knowledge transfer between science and industry.
Keywords: accessible/inclusive tourism; curriculum development; customer journeys; sustainability; tourism stakeholder